Pengaruh Kualitas Produk, Brand Image Dan Kepuasan Konsumen Terhadap Loyalitas Pelanggan Kartu Tri - Haryeni, Haryeni; Agus, Taufik; Yendra, Nofri (Jurnal Ekonomika Dan Bisnis (JEBS), 2021)
The purpose of this study was to determine: 1) The effect of product quality on consumer loyalty using the Tri cellular network, 2) The effect of brand image on consumer loyalty using the Tri cellular network, 3) The effect of consumer satisfaction on consumer loyalty using the Tri cellular network, 4) The effect of quality product, brand image, and consumer satisfaction together on consumer loyalty using the Tri cellular network.The population in this study were all students of Dharma Andalas University, Faculty of Economics and Business, Department of S1 Management, class of 2017 and 2018. The sampling in this study used the Slovin formula with the number of research samples as many as 137 respondents. The data analysis technique used in testing this research hypothesis is the use of the SPSS program. Product quality variable has a positive and significant effect on consumer loyalty. The brand image variable has a positive and significant effect on consumer loyalty. The variable of consumer satisfaction has a positive and significant effect on consumer loyalty. The variables of product quality, brand image, and customer satisfaction together have a positive and significant effect on consumer loyalty.